DANGEROUS LIAISONS: A DIALOGUE ABOUT TIES THAT BIND AND LINES THAT DIVIDE - Bradbury, Jill; Ndlovu, Siyanda (PINS-Psychology in Society, 2025)
This article offers a dialogical exploration of “race” and national identity. The argument is developed along three trajectories: 1) theoretical, drawing on the insights of Anderson, Appiah, Gilroy, Mama, Nussbaum, Ratele and others; 2) empirical, drawing on narrative interviews with black participants of different national origin, and on practical development work with South African youth; 3) personal, reflecting dynamism and oscillation in our individual positions in dialogue with one another. Bradbury’s initial position that in a society like South Africa, the “imagined community” (Anderson, 1983) of the nation may serve to undercut divisions based on “race” (and class), is challenged by the emergence of xenophobic difference. Ndlovu’s initial position that black identity is fragmented and multiple, is challenged by the possibilities for identifications based on “race” to overcome lines of difference drawn by national or other dimensions of identity. By juxtaposing our positions, we argue that neither “race” nor national identity can be simply erased and that, although there are both theoretical difficulties and political dangers entailed in these identifications, fluid and contingent interpretations may offer emancipatory possibilities.